Optimizing the location of potato logistics distribution centers using fuzzy AHP - Rindra Yusianto; Rabei Raad Ali; Pulung Nurtantio Andono (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Potato logistics and supply chains in Central Java, Indonesia, in 2025 are experiencing high price fluctuations, with price control usually in the hands of distribution centres. It limits farmers' bargaining power. In addition, the current distribution centre locations are largely inefficient. Therefore, the objective of this study is to determine the most optimal distribution centre location to support price fairness at the farmer level and improve supply chain logistics efficiency. The method used is multi-criteria decision-making (MCDM), namely the Analytic Hierarchy Process (AHP) and the Fuzzy AHP. These two methods are used to compare and evaluate alternative locations. In this study, four decision criteria were considered, namely transportation conditions, raw material availability, market location, and labour wages. The alternatives evaluated were Boyolali, Magelang, Wonosobo, and Semarang. Furthermore, expert assessments were collected from five respondents, including logistics practitioners, academics, entrepreneurs, and distributors. The results of the AHP study show that the market location variable has the highest priority weight (0.4536), followed by transportation conditions (0.2860), raw material availability (0.1602), and labour wages (0.1002). Based on AHP, the composite weights for the Boyolali, Magelang, Wonosobo, and Semarang alternatives are 0.2735, 0.1565, 0.4986, and 0.0714, respectively. Further research is recommended to combine the Analytic Network Process (ANP) to capture the interdependence between decision-making criteria.